Effectiveness Evaluation of Risk-Based SMKP Minerba Audit in Loading-Hauling-Dumping Activities for High Potential Incident Control in Open-Pit Coal Mining - Hertanti Kusuma Wardani; Dwi Yolanda Sumbung; Reynata Fachrian Tambunan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study evaluates the effectiveness of risk-based audit implementation of the Mineral and Coal Mining Safety Management System (SMKP Minerba) in loading-hauling-dumping activities for controlling High Potential Incidents (HPI) in open-pit coal mines. Loading-hauling-dumping is a core production sequence with high exposure to mobile equipment interaction, haul-road conditions, dumping-point stability, operator fatigue, blind spots, braking failure, and communication breakdown. The study adopts a mixed-methods approach with an evaluative case study design. Quantitative analysis is used to assess audit scores, HPI frequency, corrective action close-out, critical control verification, and the audit effectiveness index. Qualitative analysis is used to examine implementation gaps, control quality, supervisory practices, and barriers to completing audit findings. Data sources include SMKP audit documents, HPI and near-miss reports, corrective action registers, haul-road inspection records, pre-start inspection reports, fatigue or fit-to-work records, field observations, and semi-structured interviews with operational and safety personnel. The proposed evaluation framework integrates audit compliance score, critical control verification score, corrective action realization, and HPI reduction performance. Academic simulation results indicate that risk-based SMKP auditing can improve audit performance, strengthen critical control verification, reduce repeated findings, and decrease HPI rate. However, the close-out of major findings and overdue corrective actions remain important improvement areas. The study contributes an operational audit framework that shifts SMKP evaluation from administrative compliance toward risk-based assurance, emphasizing the prevention of fatal and serious incident potential in open-pit coal mining operations.